Material box for low-oxygen sintered neodymium-iron-boron permanent magnet material and preparation method of material box
By using a mixture of coarse alloy particles of cerium and iron elements and a high-entropy alloy box in the NdFeB permanent magnet material box, combined with laser cladding of the antioxidant layer, the problem of insufficient protective performance of the material box is solved, and significantly improved the Performance and stability of magnets.
Patent Information
- Application Number
- CN202411344311.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-20
AI Technical Summary
The existing NdFeB permanent magnet material box has limited protective performance during sintering, which can easily lead to oxidation and affect magnet performance.
The alloy coarse particles are used as the interlayer material, including cerium and iron, and are uniformly dispersed by gasoline. The alloy coarse particles preferentially react with oxygen during the sintering process to reduce oxidation; at the same time, high-entropy alloy box and laser cladding antioxidant layer are used. Improve antioxidant performance and high temperature stability.
It effectively reduces the oxidation phenomenon of neodymium iron boron permanent magnet materials, improves the magnetic performance and stability of magnets, provides better anti-oxidation protection, and ensures a low-oxygen sintering environment.
Smart Images

Figure CN119170400A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sintering of NdFeB materials, and in particular to a material box for low-oxygen sintered NdFeB permanent magnet materials and a preparation method thereof. Background Art
[0002] With the expansion of NdFeB applications, sintered NdFeB is developing towards high performance and low cost. Low oxygen content is a necessary condition for making high performance and low cost permanent magnet materials. The rare metal raw materials used in NdFeB permanent magnet materials are chemically active and are made by powder metallurgy. Especially in the powder state, they are very easy to react with oxygen.
[0003] When NdFeB pressed blanks are put into the sintering furnace, iron and graphite boxes are generally used in the industry. Iron boxes are easy to deform under high temperature and rapid cooling conditions. During the sintering process, the sintering furnace has a certain pressure rise rate, and some air will inevitably enter, causing the pressed blanks to not be well protected during the sintering process and increasing the oxygen content. Graphite boxes will not deform under high temperature and rapid cooling conditions, and the protection effect is better than that of iron boxes. However, due to the relatively low density of graphite materials, it is inevitable to absorb moisture during the production process, and the material of graphite will gradually become loose during use, and the moisture absorption phenomenon will become more and more serious. Moisture (water) will also increase the oxygen content of the magnet. In addition, the carbon element of graphite will inevitably enter the magnet at high temperature, seriously reducing the performance of the magnet. The protection performance of the existing boxes is limited, so it needs to be improved. Summary of the invention
[0004] In order to improve the anti-oxidation protection performance of a material box for NdFeB permanent magnet materials, the present application provides a material box for low-oxygen sintered NdFeB permanent magnet materials and a preparation method thereof.
[0005] The present application provides a low-oxygen sintered NdFeB permanent magnet material box and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a low-oxygen sintered NdFeB permanent magnet material box, which adopts the following technical solution: A material box for low-oxygen sintered NdFeB permanent magnet material, comprising a material box and a mixture of alloy coarse particles, wherein the mixture of alloy coarse particles is installed in an interlayer of the material box, the mixture of alloy coarse particles comprises alloy coarse particles and gasoline, and the alloy coarse particles comprise the following components in percentage by mass: Cerium 20-85% Iron 15-80%.
[0006] By installing the alloy coarse particle mixture in the interlayer of the material box, the cerium and iron elements in the alloy react with oxygen preferentially during the sintering process to prevent the NdFeB permanent magnet material in the material box from being oxidized; gasoline can help the alloy coarse particles to be evenly dispersed, reduce the contact of the alloy coarse particles with air, and reduce the oxidation of the alloy coarse particles, so that the alloy coarse particle mixture can better protect the NdFeB permanent magnet material and reduce the occurrence of oxidation.
[0007] Preferably, the raw materials for preparing the alloy coarse particles include 50-60% cerium and 40-50% iron.
[0008] According to the above ratio, the coarse alloy particles can better protect the NdFeB permanent magnet material. The cerium element has good oxygen absorption characteristics. The iron element can adjust the mechanical strength of the coarse alloy particles and at the same time regulate the oxygen absorption performance of the cerium element so that it can better combine with oxygen and enhance the protection effect on the NdFeB permanent magnet material.
[0009] Preferably, the molecular weight of the gasoline is less than 350.
[0010] Gasoline with a molecular weight less than 350 is easy to volatilize. While protecting the coarse particles of the alloy, it can volatilize under low temperature conditions and will not react with the NdFeB permanent magnet material, reducing the impact on product performance.
[0011] Preferably, the alloy coarse particle mixture is prepared by the following steps: Put cerium and iron into a crucible of a vacuum quick-setting furnace, evacuate the crucible, fill it with high-purity argon gas, start heating and melting, and obtain alloy liquid; pour the alloy liquid onto a rotating cooling copper roller, and cool it with cooling water in the copper roller to obtain alloy sheets; The alloy flakes are placed in a hydrogen crushing furnace, and high-purity hydrogen is introduced after vacuuming to carry out hydrogen crushing reaction. During the reaction, the furnace body rotates slowly, and the furnace body is cooled by circulating water. The reaction is stopped when the hydrogen pressure no longer changes, and the alloy coarse particles are obtained. The alloy coarse particles are collected in a sealed can, gasoline is added into the sealed can, and the sealed can is fixed on a three-dimensional mixer for mixing to obtain an alloy coarse particle mixture.
[0012] The alloy coarse particles prepared according to the above steps have good oxygen absorption performance and can effectively protect the NdFeB permanent magnet material; during the sintering process, the alloy coarse particles first undergo a dehydrogenation reaction, and the generated hydrogen will improve the furnace environment, and then the dehydrogenated ferrocerium will preferentially react with oxygen to prevent the permanent magnet material in the material box from being oxidized.
[0013] Preferably, the material box comprises a high entropy alloy box body and a laser cladding anti-oxidation layer.
[0014] High entropy alloys have good high-temperature stability, can remain stable at high temperatures during sintering, are not prone to deformation and damage, do not react with permanent magnetic materials, and avoid contaminating permanent magnetic materials; the composition of high entropy alloys is uniform, so that the NdFeB permanent magnetic materials can react evenly when heated during sintering, thereby improving the magnetic properties of the product; the laser cladding anti-oxidation layer can protect the high entropy alloy box, improve its anti-oxidation properties, and reduce the possibility of high entropy alloy being oxidized, thereby improving its stability, providing a stable sintering environment, and further reducing the interaction between permanent magnetic materials and the box, thereby improving the magnetic properties of the product.
[0015] Preferably, the raw materials for preparing the high entropy alloy box body include niobium, molybdenum, tantalum nitride, tungsten and hafnium.
[0016] The high-entropy alloy prepared by niobium, molybdenum, tantalum nitride, tungsten and hafnium has good high-temperature stability. Hafnium and nitrogen elements generate hafnium nitride ceramic phase during the smelting process, which is evenly dispersed inside the high-entropy alloy, reducing the grain size of the high-entropy alloy, improving the strength of the high-entropy alloy through fine grain strengthening and dispersion strengthening, and reducing the occurrence of deformation of the high-entropy alloy material box.
[0017] Preferably, the laser cladding anti-oxidation layer is obtained by laser cladding a cladding mixture, and raw materials for preparing the cladding mixture include silicon nitride and bonding alloy powder.
[0018] Preferably, the raw materials for preparing the bonding alloy powder include the following components in percentage: chromium 13.5-16.3%, aluminum 10.5-12.8%, nickel 17.5-19.3%, and the balance is iron.
[0019] By laser cladding the anti-oxidation layer, the oxidation resistance and high-temperature stability of the high-entropy alloy box body are improved. The silicon nitride ceramic phase material and the alloy that plays a bonding role are mixed and clad on the surface of the high-entropy alloy box body, which improves the bonding strength between the silicon nitride ceramic phase and the high-entropy alloy box body, so that the ceramic phase can better improve the high-temperature stability of the high-entropy alloy box body, reduce the adhesion of the permanent magnetic material to the material box, and thus improve the magnetic properties of the permanent magnetic material; the bonding alloy powder has good oxidation resistance and corrosion resistance according to the above ratio, can effectively protect the high-entropy alloy box body, and at the same time has good bonding performance, so that the silicon nitride ceramic phase is evenly clad on the surface of the high-entropy alloy box body.
[0020] In a second aspect, the present application provides a method for preparing a material box for low-oxygen sintered NdFeB permanent magnet material, using the following technical solution: A method for preparing a material box for low-oxygen sintered NdFeB permanent magnet material comprises the following steps: The oxide layers of niobium, molybdenum and hafnium are removed by sandpaper, and the niobium, molybdenum and hafnium are washed by ultrasonic oscillation in anhydrous ethanol to obtain pretreated niobium, molybdenum and hafnium, tantalum nitride powder and tungsten powder are placed at the bottom of the crucible, and niobium, molybdenum and hafnium are placed on the top, and vacuum arc melting is performed, and after vacuuming, the air is washed, and the vacuum is again evacuated to negative pressure, and argon gas is introduced, and arc melting is performed, and the arc is extinguished and cooled after melting, and the melting is repeated 4-6 times, and a high entropy alloy ingot is obtained after cooling to room temperature; the high entropy alloy ingot is placed in a casting crucible table, and after vacuuming, it is melted to a liquid state, and injection molded to obtain a high entropy alloy plate; the high entropy alloy plate is cut and welded to obtain a high entropy alloy box; Silicon nitride and bonding alloy powders are mixed in a high-energy ball mill, mechanically mixed in an argon environment to obtain a cladding mixture, and the cladding mixture is used to laser clad a high-entropy alloy box body to prepare a laser cladding anti-oxidation layer to obtain a material box; the alloy coarse particle mixture is loaded into the interlayer to obtain a material box for low-oxygen sintered NdFeB permanent magnet materials.
[0021] The low-oxygen sintered NdFeB permanent magnet material box prepared according to the above steps has good high-temperature stability, can effectively protect the NdFeB magnet material, and reduce the occurrence of oxidation.
[0022] Preferably, the material box for low-oxygen sintered NdFeB permanent magnet material includes a bottom plate, an inner surrounding wall, and an outer surrounding wall, the inner surrounding wall and the outer surrounding wall are fixedly arranged on the bottom plate, the inner surrounding wall is located inside the outer surrounding wall and is spaced apart from each other with an interlayer, the inner surrounding wall includes an inner side plate and an inner bevel plate, the outer wall includes an outer side plate and an outer bevel plate, the inner side plate and the outer side plate are arranged in four pieces around the center of the bottom plate, adjacent inner side plates are perpendicular to each other, adjacent outer side plates are perpendicular to each other, the inner bevel plate is arranged between adjacent inner side plates, the outer bevel plate is arranged between adjacent outer side plates, one side of the inner bevel plate is connected to one of the inner side plates, the other side of the inner bevel plate is connected to the other inner plate, one side of the outer bevel plate is connected to one of the outer plates, the other side of the outer bevel plate is connected to the other outer plate, and the interlayer is filled with a mixture of coarse alloy particles.
[0023] By setting bevel plates at the four corners of the material box, the oxidation of the NdFeB permanent magnet material at the edge of the material box can be reduced. The bevel plates can also effectively disperse the stress and reduce the deformation of the material box. The interlayer is filled with a mixture of coarse alloy particles to provide good anti-oxidation protection for the NdFeB permanent magnet material, control oxygen penetration, and create a low-oxygen environment, thereby improving the performance of the NdFeB permanent magnet material.
[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. By installing the alloy coarse particle mixture in the interlayer of the material box, the cerium and iron elements in the alloy react with oxygen preferentially during the sintering process to prevent the NdFeB permanent magnet material in the material box from being oxidized; gasoline can help the alloy coarse particles to be evenly dispersed, reduce the contact of the alloy coarse particles with air, and reduce the oxidation of the alloy coarse particles, so that the alloy coarse particle mixture can better protect the NdFeB permanent magnet material and reduce the occurrence of oxidation.
[0025] 2. High entropy alloy has good high-temperature stability, can remain stable at high temperatures during sintering, is not prone to deformation and damage, does not react with permanent magnetic materials, and avoids contamination of permanent magnetic materials; the composition of high entropy alloy is uniform, so that the NdFeB permanent magnetic material can react evenly during sintering, thereby improving the magnetic properties of the product; the laser cladding anti-oxidation layer can protect the high entropy alloy box, improve its anti-oxidation performance, and reduce the possibility of high entropy alloy being oxidized, thereby improving its stability, providing a stable sintering environment, further reducing the interaction between permanent magnetic materials and the box, and improving the magnetic properties of the product.
[0026] 3. By setting bevel plates at the four corners of the material box, the oxidation of the NdFeB permanent magnet material at the edge of the material box is reduced. The bevel plates can also effectively disperse the stress and reduce the deformation of the material box. The interlayer is filled with a mixture of coarse alloy particles to provide good anti-oxidation protection for the NdFeB permanent magnet material, control oxygen penetration, and create a low-oxygen environment, thereby improving the performance of the NdFeB permanent magnet material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic structural diagram of a material box for low-oxygen sintered NdFeB permanent magnet material of the present invention.
[0028] Explanation of the reference numerals: 1. bottom plate; 2. inner wall; 21. inner side plate; 22. inner bevel plate; 3. outer wall; 31. outer side plate; 32. outer bevel plate; 4. interlayer. DETAILED DESCRIPTION
[0029] The present application discloses a material box for low-oxygen sintered NdFeB permanent magnet material and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. Figure 1 The present application is further described in detail with examples: Reference Figure 1A low-oxygen sintered NdFeB permanent magnet material box comprises a bottom plate 1, an inner wall 2, and an outer wall 3. The inner wall 2 and the outer wall 3 are fixedly arranged on the bottom plate 1. The inner wall 2 is located inside the outer wall 3 and interlayers 4 are arranged at intervals. The inner wall 2 comprises an inner side plate 21 and an inner bevel plate 22. The outer wall 3 comprises an outer side plate 31 and an outer bevel plate 32. The inner side plate 21 and the outer side plate 31 are arranged in four pieces around the center of the bottom plate 1. The adjacent inner plates 21 are perpendicular to each other, and the adjacent outer plates 31 are perpendicular to each other. The inner bevel plates 22 are arranged at adjacent inner sides. The outer bevel plate 32 is arranged between the side plates 21, and the outer bevel plate 32 is arranged between the adjacent outer plates 31, so as to reduce the oxidation at the corners of the NdFeB permanent magnet material, disperse the stress, and reduce the deformation of the material box; one side of the inner bevel plate 22 is connected to one of the inner plates 21, and the other side of the inner bevel plate 22 is connected to the other inner plate 21, one side of the outer bevel plate 32 is connected to one of the outer plates 31, and the other side of the outer bevel plate 32 is connected to the other outer plate 31, and the interlayer 4 is filled with a mixture of coarse alloy particles to protect the NdFeB permanent magnet material from oxidation.
[0030] Example 1 Preparation of alloy coarse particle mixture 50kg of cerium and 50kg of iron are put into the crucible of a vacuum rapid solidification furnace, evacuated to below 0.1Pa, filled with high-purity argon to 60KPa, and heated to melt to obtain alloy liquid; the alloy liquid is poured onto a rotating cooling copper roller, cooled by cooling water in the copper roller to obtain an alloy sheet with a thickness of about 0.3mm.
[0031] The alloy sheets are loaded into a hydrogen crushing furnace, evacuated to below 0.1Pa, and high-purity hydrogen is introduced. After the pressure reaches 90KPa, a hydrogen crushing reaction is carried out. During the reaction, the furnace body rotates slowly at a speed of 4r / min, and the furnace body is cooled with circulating water. The reaction is stopped after the hydrogen pressure no longer changes to obtain alloy coarse particles with a diameter of 0.5-1mm. The alloy coarse particles are collected in a sealed can, and No. 120 gasoline is added to the sealed can. The volume ratio of the alloy coarse particles to No. 120 gasoline is 1:1. The sealed can is fixed on a three-dimensional mixer for mixing for 2 hours to obtain an alloy coarse particle mixture.
[0032] Preparation of material box The oxide layer of niobium, molybdenum and hafnium was removed by sandpaper, and the niobium, molybdenum and hafnium were washed with ultrasonic oscillation in anhydrous ethanol for 30 minutes to obtain pretreated niobium, molybdenum and hafnium. The pretreated niobium, molybdenum, hafnium and tantalum nitride powder and tungsten powder were weighed in a molar ratio of 1:1:1:1:1. The tantalum nitride powder and tungsten powder were placed at the bottom of the crucible, and niobium, molybdenum and hafnium were placed on the top for vacuum arc melting. After vacuuming to 2Pa, the air was washed twice and vacuumed again to 5*10 -3Pa, argon is introduced to 40KPa, arc melting is started, the current is 350A, arc is extinguished and cooled after melting for 5min, and the melting is repeated 4 times. After cooling to room temperature, a high entropy alloy ingot is obtained. The high entropy alloy ingot is placed in a casting crucible, evacuated and melted to liquid state, and injection molded to obtain a high entropy alloy sheet. After the high entropy alloy sheet is cut and welded, a high entropy alloy box is obtained.
[0033] Silicon nitride and bonding alloy powder are mixed in a high-energy ball mill at a mass ratio of 1:20. The bonding alloy powder contains the following percentages of elements: chromium 13.5%, aluminum 10.5%, nickel 17.5%, and iron 58.5%. The powder is mechanically ball-mixed at a speed of 150r / min for 5 hours in an argon environment to obtain a cladding mixture. The cladding mixture is used to laser clad a high-entropy alloy box body to prepare a laser cladding anti-oxidation layer. The laser scanning speed is 10mm / s, the laser spot diameter is 3mm, the powder feeding speed is 12g / min, the laser power is 2kW, and the argon flow rate is 15L / min to obtain a material box. The alloy coarse particle mixture is loaded into the interlayer to obtain a material box for low-oxygen sintered NdFeB permanent magnet materials.
[0034] Example 2 Preparation of alloy coarse particle mixture 60kg of cerium and 40kg of iron are put into the crucible of a vacuum rapid solidification furnace, evacuated to below 0.1Pa, filled with high-purity argon to 60KPa, and heated to melt to obtain alloy liquid; the alloy liquid is poured onto a rotating cooling copper roller, cooled by cooling water in the copper roller to obtain an alloy sheet with a thickness of about 0.3mm.
[0035] The alloy sheets are loaded into a hydrogen crushing furnace, evacuated to below 0.1Pa, and high-purity hydrogen is introduced. After the pressure reaches 90KPa, a hydrogen crushing reaction is carried out. During the reaction, the furnace body rotates slowly at a speed of 5r / min, and the furnace body is cooled with circulating water. The reaction is stopped after the hydrogen pressure no longer changes to obtain alloy coarse particles with a diameter of 0.5-1mm. The alloy coarse particles are collected in a sealed can, and No. 120 gasoline is added to the sealed can. The volume ratio of the alloy coarse particles to No. 120 gasoline is 1:1. The sealed can is fixed on a three-dimensional mixer for mixing for 3 hours to obtain an alloy coarse particle mixture.
[0036] Preparation of material box The oxide layer of niobium, molybdenum and hafnium was removed by sandpaper, and the niobium, molybdenum and hafnium were washed with ultrasonic oscillation in anhydrous ethanol for 30 minutes to obtain pretreated niobium, molybdenum and hafnium. The pretreated niobium, molybdenum, hafnium and tantalum nitride powder and tungsten powder were weighed in a molar ratio of 1:1:1:1:1. The tantalum nitride powder and tungsten powder were placed at the bottom of the crucible, and niobium, molybdenum and hafnium were placed on the top for vacuum arc melting. After vacuuming to 2Pa, the air was washed twice and vacuumed again to 5*10 -3Pa, introduce argon to 40KPa, start arc melting, current 350A, smelt for 5min and then extinguish arc to cool, repeat smelting 6 times, and obtain high entropy alloy ingot after cooling to room temperature. Place the high entropy alloy ingot in a casting crucible, evacuate and melt to liquid, and inject mold to obtain high entropy alloy sheet. Cut and weld the high entropy alloy sheet to obtain a high entropy alloy box.
[0037] Silicon nitride and bonding alloy powder were mixed in a high-energy ball mill at a mass ratio of 1:20. The bonding alloy powder contained the following percentages of elements: 16.3% chromium, 12.8% aluminum, 19.3% nickel, and 51.6% iron. The powder was mechanically ball-mixed at a speed of 150 r / min for 5 hours in an argon environment to obtain a cladding mixture. The cladding mixture was used to laser clad a high-entropy alloy box body to prepare a laser cladding anti-oxidation layer. The laser scanning speed was 10 mm / s, the laser spot diameter was 3 mm, the powder feeding speed was 12 g / min, the laser power was 2 kW, and the argon flow rate was 15 L / min to obtain a material box. The alloy coarse particle mixture was loaded into the interlayer to obtain a material box for low-oxygen sintered NdFeB permanent magnet materials.
[0038] Example 3 Preparation of alloy coarse particle mixture 55kg of cerium and 45kg of iron are placed in the crucible of a vacuum rapid solidification furnace, evacuated to below 0.1Pa, filled with high-purity argon to 60KPa, and heated to melt to obtain a molten alloy; the molten alloy is poured onto a rotating cooling copper roller, cooled by cooling water in the copper roller to obtain an alloy sheet with a thickness of about 0.3mm.
[0039] The alloy sheets are loaded into a hydrogen crushing furnace, evacuated to below 0.1Pa, and high-purity hydrogen is introduced. After the pressure reaches 90KPa, a hydrogen crushing reaction is carried out. During the reaction, the furnace body rotates slowly at a speed of 4.5r / min. The furnace body is cooled with circulating water. The reaction is stopped after the hydrogen pressure no longer changes to obtain alloy coarse particles with a diameter of 0.5-1mm. The alloy coarse particles are collected in a sealed can, and No. 120 gasoline is added to the sealed can. The volume ratio of the alloy coarse particles to No. 120 gasoline is 1:1. The sealed can is fixed on a three-dimensional mixer and mixed for 2.5 hours to obtain a mixture of alloy coarse particles.
[0040] Preparation of material box The oxide layer of niobium, molybdenum and hafnium was removed by sandpaper, and the niobium, molybdenum and hafnium were washed with ultrasonic oscillation in anhydrous ethanol for 30 minutes to obtain pretreated niobium, molybdenum and hafnium. The pretreated niobium, molybdenum, hafnium and tantalum nitride powder and tungsten powder were weighed in a molar ratio of 1:1:1:1:1. The tantalum nitride powder and tungsten powder were placed at the bottom of the crucible, and niobium, molybdenum and hafnium were placed on the top for vacuum arc melting. After vacuuming to 2Pa, the air was washed twice and vacuumed again to 5*10 -3Pa, introduce argon to 40KPa, start arc melting, current 350A, smelt for 5min and then extinguish the arc to cool, repeat the melting 5 times, and obtain a high entropy alloy ingot after cooling to room temperature. Place the high entropy alloy ingot in a casting crucible, evacuate and melt to liquid, and inject into a mold to obtain a high entropy alloy sheet. After cutting and welding the high entropy alloy sheet, a high entropy alloy box is obtained.
[0041] Silicon nitride and bonding alloy powder were mixed in a high-energy ball mill at a mass ratio of 1:20. The bonding alloy powder contained the following percentages of elements: chromium 14.9%, aluminum 11.65%, nickel 18.4%, and iron 55.05%. The powder was mechanically ball-mixed at a speed of 150 r / min for 5 hours in an argon environment to obtain a cladding mixture. The cladding mixture was used to laser clad a high-entropy alloy box body to prepare a laser cladding anti-oxidation layer. The laser scanning speed was 10 mm / s, the laser spot diameter was 3 mm, the powder feeding speed was 12 g / min, the laser power was 2 kW, and the argon flow rate was 15 L / min to obtain a material box. The alloy coarse particle mixture was loaded into the interlayer to obtain a material box for low-oxygen sintered NdFeB permanent magnet materials.
[0042] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the percentage of cerium in the alloy coarse particles is 20%, and the percentage of iron is 80%.
[0043] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the percentage of cerium in the alloy coarse particles is 85%, and the percentage of iron is 15%.
[0044] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, no laser cladding anti-oxidation layer is prepared when preparing the material box.
[0045] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that the alloy coarse particle mixture is replaced by alloy coarse particles in Comparative Example 1.
[0046] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that the material box in Comparative Example 2 is replaced by a tinplate material box.
[0047] Performance testing (1) GB / T13560-2017 Sintered NdFeB Permanent Magnet Material and GB / T3217-92 Magnetic Test Method for Permanent Magnet (Hard Magnetic) Material were selected as the standards to test the magnetic properties of the products sintered with the samples. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.
[0048] (2) Oxidation condition detection: Observe whether the product after sintering the sample is blackened or deformed. The results are recorded in Table 1.
[0049] Table 1 Magnetic properties and oxidation test results of products sintered using cartridges It can be seen from Table 1 that the remanence of Examples 1-3 is greater than 13.72 kGs, the coercive force is greater than 18.32 kOe, the squareness is greater than 99.1%, and there is no blackening or bending deformation. It can be seen that the material box prepared in the present application has good high temperature stability and antioxidant properties, can effectively protect NdFeB permanent magnet materials, and improve the magnetic properties of permanent magnet materials.
[0050] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that in Example 4, the percentage of cerium in the alloy coarse particles is 20%, and the percentage of iron is 80%, while in Example 5, the percentage of cerium in the alloy coarse particles is 85%, and the percentage of iron is 15%. Compared with Example 3, the magnetic properties of the products of Examples 4 and 5 are reduced, and oxidation occurs; this is because changing the ratio of cerium and iron in the ferrocerium alloy will affect the oxygen absorption performance of the alloy coarse particles, thereby affecting the oxygen content in the product, and further affecting the magnetic properties of the product.
[0051] It can be seen from Table 1 that the only difference between Example 6 and Example 3 is that in Example 6, no laser cladding anti-oxidation layer is prepared when preparing the material box. Compared with Example 3, the magnetic properties of the product in Example 6 are significantly reduced, and there is obvious oxidation. This is because without the laser cladding anti-oxidation layer, some elements in the high entropy alloy are easily oxidized, which may introduce oxygen elements during the sintering process of the permanent magnet material and reduce the magnetic properties of the product.
[0052] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the alloy coarse particle mixture is replaced with alloy coarse particles. Compared with Example 3, the magnetic properties of the product in Comparative Example 1 are significantly reduced, and the oxidation deformation is obvious; this is because gasoline is not added to disperse the alloy coarse particle mixture, and there is a lack of sealing protection. The alloy coarse particles are easily oxidized and the oxygen absorption capacity is reduced, which affects the protection of the NdFeB permanent magnet material and the magnetic properties of the product are significantly reduced.
[0053] It can be seen from Table 1 that the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the material box is replaced with a tinplate material box. Compared with Example 3, the magnetic properties of the product in Comparative Example 2 are significantly reduced, and the oxidation deformation is obvious; this is because the material box is replaced with a tinplate material box, and the tinplate material box is prone to deformation in a high temperature environment, and is easy to oxidize, has poor corrosion resistance, and is easy to contaminate the permanent magnet material during the sintering process, affecting the magnetic properties and shape of the product.
[0054] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A low-oxygen sintered NdFeB permanent magnet material box, characterized in that: It comprises a material box and a mixture of alloy coarse particles, wherein the mixture of alloy coarse particles is installed in an interlayer of the material box, the mixture of alloy coarse particles comprises alloy coarse particles and gasoline, and the alloy coarse particles comprise the following components in percentage by mass: Cerium 20-85% Iron 15-80%.
2. A low-oxygen sintered NdFeB permanent magnet material box according to claim 1, characterized in that: The raw materials for preparing the alloy coarse particles include 50-60% cerium and 40-50% iron.
3. A low-oxygen sintered NdFeB permanent magnet material box according to claim 2, characterized in that: The molecular weight of the gasoline is less than 350.
4. A low-oxygen sintered NdFeB permanent magnet material box according to claim 3, characterized in that: The alloy coarse particle mixture is prepared by the following steps: Put cerium and iron into a crucible of a vacuum quick-setting furnace, evacuate the crucible, fill it with high-purity argon gas, start heating and melting, and obtain alloy liquid; pour the alloy liquid onto a rotating cooling copper roller, and cool it with cooling water in the copper roller to obtain alloy sheets; The alloy flakes are placed in a hydrogen crushing furnace, and high-purity hydrogen is introduced after vacuuming to carry out hydrogen crushing reaction. During the reaction, the furnace body rotates slowly, and the furnace body is cooled by circulating water. The reaction is stopped when the hydrogen pressure no longer changes, and the alloy coarse particles are obtained. The alloy coarse particles are collected in a sealed can, gasoline is added into the sealed can, and the sealed can is fixed on a three-dimensional mixer for mixing to obtain an alloy coarse particle mixture.
5. The low-oxygen sintered NdFeB permanent magnet material box according to claim 1, characterized in that: The material box comprises a high entropy alloy box body and a laser cladding anti-oxidation layer.
6. A low-oxygen sintered NdFeB permanent magnet material box according to claim 5, characterized in that: The raw materials for preparing the high entropy alloy box body include niobium, molybdenum, tantalum nitride, tungsten and hafnium.
7. A low-oxygen sintered NdFeB permanent magnet material box according to claim 6, characterized in that: The laser cladding anti-oxidation layer is obtained by laser cladding a cladding mixture, and the raw materials for preparing the cladding mixture include silicon nitride and bonding alloy powder.
8. The low-oxygen sintered NdFeB permanent magnet material box according to claim 7, characterized in that: The raw materials for preparing the bonding alloy powder include the following components in percentage: 13.5-16.3% chromium, 10.5-12.8% aluminum, 17.5-19.3% nickel, and the balance is iron.
9. A method for preparing a material box for low-oxygen sintered NdFeB permanent magnet material as claimed in any one of claims 1 to 8, characterized in that: The steps include: The oxide layers of niobium, molybdenum and hafnium are removed by sandpaper, and the niobium, molybdenum and hafnium are washed by ultrasonic oscillation in anhydrous ethanol to obtain pretreated niobium, molybdenum and hafnium, tantalum nitride powder and tungsten powder are placed at the bottom of the crucible, and niobium, molybdenum and hafnium are placed on the top, and vacuum arc melting is performed, and after vacuuming, the air is washed, and the vacuum is again evacuated to negative pressure, and argon gas is introduced, and arc melting is performed, and the arc is extinguished and cooled after melting, and the melting is repeated 4-6 times, and a high entropy alloy ingot is obtained after cooling to room temperature; the high entropy alloy ingot is placed in a casting crucible table, and after vacuuming, it is melted to a liquid state, and injection molded to obtain a high entropy alloy plate; the high entropy alloy plate is cut and welded to obtain a high entropy alloy box; Silicon nitride and bonding alloy powders are mixed in a high-energy ball mill, mechanically mixed in an argon environment to obtain a cladding mixture, and the cladding mixture is used to laser clad a high-entropy alloy box body to prepare a laser cladding anti-oxidation layer to obtain a material box; the alloy coarse particle mixture is loaded into the interlayer to obtain a material box for low-oxygen sintered NdFeB permanent magnet materials.
10. The method for preparing a material box for low-oxygen sintered NdFeB permanent magnet material according to claim 9, characterized in that: The low-oxygen sintered NdFeB permanent magnet material box comprises a bottom plate (1), an inner surrounding wall (2), and an outer wall (3); the inner surrounding wall (2) and the outer wall (3) are both fixedly arranged on the bottom plate (1); the inner surrounding wall (2) is located inside the outer wall (3) and interlayers (4) are arranged at intervals; the inner surrounding wall (2) comprises an inner side plate (21) and an inner bevel plate (22); the outer wall (3) comprises an outer side plate (31) and an outer bevel plate (32); the inner side plate (21) and the outer side plate (31) are arranged in four pieces around the center of the bottom plate (1); adjacent inner side plates (21) are spaced apart from each other. The outer plates (31) are perpendicular to each other, the inner bevel plate (22) is arranged between adjacent inner plates (21), and the outer bevel plate (32) is arranged between adjacent outer plates (31). One side of the inner bevel plate (22) is connected to one of the inner plates (21), and the other side of the inner bevel plate (22) is connected to the other inner plate (21). One side of the outer bevel plate (32) is connected to one of the outer plates (31), and the other side of the outer bevel plate (32) is connected to the other outer plate (31). The interlayer (4) is filled with a mixture of alloy coarse particles.
